Enhancing experiential learning through community debriefs: A reflection from facilitators of experiential games - Melesse, Mequanint B.; Duche, Vishwambhar; Sanil, Richu; Meinzen-Dick, Ruth S.; Falk, Thomas (International Food Policy Research Institute, 2024)
Community debriefing is a structured process that facilitates the sharing of experience and insights about implemented interventions among community members. It enables participants to connect lessons learned in an activity, experience, or program to the outside world and to discuss the relevance of an activity to the challenges faced by the community. Thus, social learning is reinforced when debriefing sessions are conducted at the community level. Here, we are interested in debriefings conducted after playing experiential learning games as a learning space beyond the game itself.